Metode Fun Creative Learning dalam Pengajaran Pendidikan Agama Islam di Sekolah Dasar Islam Fase B - Rakha Ryanki Farhan; Abas Mansur Tamam; Ulil Amri Syafri (Al-Liqo: Jurnal Pendidikan Islam, 2022)
The Fun Creative Learning method is a fun learning strategy to create an effective learning environment, designed in such a way as to provide an atmosphere that is full of fun and most importantly not saturating and boring.  The fun creative learning method is an easy way to educate early childhood because it suits their needs and stage of development. This research aims to find out the fin creative learning method applied at the 4th grade level of Islamic Elementary School between SDIT Al-Hidayah Bogor and SDIT SUIS (Sekolah Unggulan Islam) Bogor.  As well as formulating a Fun Creative Learning Method that is extracted from the main sources of Al-Qur'an and As-Sunnah, and will be enriched with the thoughts of experts on the method. This research is a type of qualitative and field research.  This research is descriptive in nature by taking the object of study at SDIT Al-Hidayah Bogor and SDIT SUIS Bogor.  The data collection techniques used in this research are documentation, informant interviews, observation, and focus group discussion (FGD). The results obtained from this research are a fun creative learning method according to educational experts which contains teaching techniques from each method given.